Dienogest. A possible conservative approach in bladder endometriosis. Results of a pilot study. (May 2015) - Angioni, Stefano; Nappi, Luigi; Pontis, Alessandro; Sedda, Federica; Luisi, Stefano; Mais, Valerio; Melis, Gian Benedetto
Abstract Deep endometriosis involvement of the bladder is uncommon but it is symptomatic in most of the cases. Although laparoscopic excision is very effective, some patients with no pregnancy desire require a medical approach. We performed a pilot study on the effect of a new progestin dienogest on bladder endometriosis. Six patients were treated for 12 months with dienogest 2 mg/daily. Pain, urinary symptoms, quality of life, nodule volume and side effects were recorded. During treatment, symptoms improved very quickly and the nodules exhibit a remarkable reduction in size. Dienogest may be an alternative approach to bladder endometriosis.